Improving Information Technology Service Management Effectiveness through ITIL Implementation at SMPN 7 IT Manggelewa - Hardyanti; Yuyun Yuningsih RS; Maylisda Naomi Loko (Decode: Jurnal Pendidikan Teknologi Informasi, 2025)
Information Technology (IT) services are essential in enhancing the efficiency of administrative and learning processes in schools. However, many public junior high schools still manage IT services manually, without clear documentation or standard operating procedures, which leads to delayed responses, system unreliability, and low user satisfaction. This study aims to improve the effectiveness of IT service management at SMPN 7 IT Manggelewa through the implementation of a simplified model based on the ITIL (Information Technology Infrastructure Library) Service Operation framework. Employing a qualitative descriptive approach with an evaluative and model development orientation, data were collected through observations, interviews, document analysis, and questionnaires involving school stakeholders. The findings reveal major gaps between current practices and ITIL standards across five key processes: Incident Management, Request Fulfillment, Access Management, Problem Management, and Event Management. As a result, a contextualized ITIL-based model was developed, including SOPs, service request forms, access control procedures, a root-cause analysis template, and manual monitoring tools. The model was validated through a focus group discussion and revised for school-level applicability. This study concludes that the application of a school-adapted ITIL model improves service responsiveness, documentation practices, and stakeholder accountability in managing IT services.